Screened Intimacies: Tinder and the Swipe Logic - Gaby David; Carolina Cambre (Social Media + Society, 2016)
This article seeks to amplify discursive constructions of social connection through technology with an examination of the proposed and presumed intimacies of the Tinder app. In the first half, we ethnographically examine the sociotechnical dynamics of how users navigate the app and take up or resist the subject positions encouraged by the user interface feature of swiping. In the second half, we provide a discussion of the implications of the swipe logic through post-structural conceptual lenses interrogating the ironic disruption of intimacy of Tinder’s interface.